HUBUNGAN KADAR ZINK DALAM ASI DENGAN BERAT BADAN DAN PANJANG BADAN BAYI USIA 4-6 BULAN DI KOTA PADANG SUMATERA BARAT - Ratnadewi Ratnadewi (Jurnal Akademika Baiturrahim Jambi, 2019)
Zinc deficiency is public health problem. Almost two million people in developing country suffered zinc deficiency. Zinc deficiency in Indonesia, 25% in breastfeeding mothers and 17% in babies. The purpose of this study was to determine the correlation of zinc level in breastmilk with 4-6 months old baby weight and length in Padang City West Sumatera. This study was done in working area of Lubuk Buaya, Padang Pasir, and Nanggalo Public Health Center. This study was done from January 2016 until January 2017. The design of this study was cross sectional, number of sample were 108 people. Samples were selected by simple random sampling. Zinc level in breastmilk was checked by AAS (Atomic Absorption Spectrophotometer). Data were analyzed by using univariate and bivariate with pearson correlation test. The correlation test, correlation was positive and patterned between log zinc level in breastmilk with 4-6 months old baby weight (r=0,272), while the length (r=0,216), correlation was positive and weak with p value <0,05. That there were significant correlation between log zinc level in breastmilk and 4-6 months old baby weight and length.